Distribution, characterization, and antibiotic resistance of hypervirulent Klebsiella pneumoniae isolates in a Chinese population with asymptomatic bacteriuria - Li, Jun; Li, Yanbing; Tang, Mengli; Xia, Fengjun; Min, Changhang; Hu, Yongmei; Wang, Haichen; Zhang, Jingyi; Zou, Mingxiang (BMC microbiology, 2022)
Asymptomatic bacteriuria (ASB) frequently occurs among all ages and may develop into urinary tract infections (UTIs). Hypervirulent Klebsiella pneumoniae (hvKP) has become a new threat to human health. In our study, we aimed to investigate the epidemiological characteristics of hvKP in population with ASB. A total of 61 K. pneumoniae isolates were collected from 7530 urine samples between October and December 2020. The strains were sensitive to most of the antimicrobial agents tested, but a polymyxin resistant strain was found (MIC>16 μg/mL). Three serotypes were detected, including K1 (16.4%, 10/61), K5 (1.6%, 1/61) and K57 (3.2%, 2/61). Four strains (KPNY9, KPNY31, KPNY40, and KPNY42) carried a combination of two or more hypervirulent markers (peg-344, iroB, iucA, rmpA, and rmpA2), and their survival rates after Galleria mellonella infection were lower than those of the other strains (40.0 vs. 70.0%), suggesting that they were hvKP. These hvKP strains with lower biofilm forming ability than classical K. pneumoniae (0.2625 ± 0.0579 vs. 0.6686 ± 0.0661, P = 0.033) were identified as belonging to K2-ST65, K2-ST86, K57-ST592, and K2-ST5559 (a new ST type). KPNY31 (ST5559) shared a close genetic relationship with KPNY42 (ST86) and other ST86 isolates, which have been detected in both nosocomial and community-acquired infections. The hvKP with relatively weak biofilm formation was detected in a population with ASB, which was more likely to cause bacteremia and serious consequences. A novel sequence type (ST5559) hvKP derived from ST86 was found. Therefore, hvKP should be monitored in the population with ASB.